Theoretical analysis and evaluation for neutron-induced reaction on 239Pu. (October 2017) - Guo, Hairui; Han, Yinlu; Ye, Tao; Sun, Weili; Cai, Chonghai
Highlights: The nuclear data of n+ 239 Pu reaction are obtained at the incident energies up to 200 MeV. The information of proton, deuteron, triton, helium-3 and alpha emissions is provided in the nuclear data. The n + 239 Pu reaction is consistently calculated and analyzed by theoretical nuclear models. The present results are in good agreement with the experimental data generally. Abstract: The nuclear data of n+ 239 Pu reaction for the incident energy up to 200 MeV are currently required for the study of new-generation nuclear systems. To meet this requirement, all cross sections, angular distributions, energy spectra, double differential cross sections of neutron, proton, deuteron, triton, helium-3 and alpha emissions and the number of neutron per fission for n+ 239 Pu reaction are consistently calculated and analyzed by theoretical nuclear models in the energy range of E n ⩽ 200 MeV . The theoretical models include the optical model, the distorted wave Born approximation theory, the Hauser-Feshbach theory, the fission model, the evaporation model, the exciton model and the intranuclear cascade model. The calculated results are compared with recent experimental data and the evaluated data from ENDF/B-VII and JENDL-4.